Transvaginal high uterosacral ligament suspension: An alternative to McCall culdoplasty in the treatment of pelvic organ prolapse. (September 2019) - Novara, Lorenzo; Sgro, Luca Giuseppe; Pecchio, Silvia; Ottino, Laura; Tomatis, Veronica; Biglia, Nicoletta
Abstract: Objectives: Defects in female pelvic organ support are highly prevalent. Uterosacral ligament suspension at the time of primary prolapse repair (McCall culdoplasty) is a well-established surgical option to prevent prolapse recurrences. Recently Shull's high uterosacral ligament suspension technique has gained increasing popularity among Uro-Gynaecologists. A study carried out in 2017 by Spelzini et al. compared these two techniques, showing proper safety and efficacy in the treatment of prolapse, with no statistically significant differences as to operative time, complication rate, anatomical, functional and subjective outcomes [1 ]. Our study aims at comparing the effectiveness, complication rate, recurrence rate, quality of life and functional result of the two techniques. Study design: This is a retrospective study carried out on 224 patients who underwent vaginal cuff suspension for pelvic organ prolapse. Cases were extracted from hospital medical records of all women managed with surgical prolapse repair at our Gynaecology and Obstetrics department between January 2013 and February 2017. Shull suspension (group A) or McCall culdoplasty (group B) were performed according to surgeon's familiarity with the two suspension techniques. Results: A total of 224 patients (69 in group A and 155 in group B) underwent surgical cuff suspension. Median operating time was 88 min for both techniques and ureteral injuries were very rare in both group A and B (1 and 0 respectively). In the evaluation of postoperative questionnaires, no statistically significant differences were found, except for "Urinary Impact Questionnaire" (UIQ), which showed significantly less urinary subjective symptoms in group A. Median follow up was 13 months in group A and 15 months in group B. Post-operative Pop-Q items analysis revealed only a higher Aa point in group A at 12 months follow up visit. Objective vaginal cuff recurrence was observed in 1 patient (1, 4%) in group A and 4 patients in group B (2, 6%) with no statistically significant difference between the two groups. Conclusions: Both uterosacral ligament suspension procedures are safe and highly effective. There were no statistically significant differences concerning surgical data, complication rates, and the majority of anatomical, functional and subjective outcomes between Shull suspension and McCall culdoplasty.